Effect of PH on stress corrosion cracking of stainless steel [electronic resource] - Nurul Fadhilah Tajuddin, 1988-; Yunan Prawoto, supervisor; Fakulti Kejuruteraan Mekanikal (2011)
Project Paper (Sarjana Muda Kejuruteran (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2011